Mulheres com neoplasia mamária em tratamento quimioterápico ou em hormonioterapia: uma avaliação da qualidade de vida - Cordeiro, Laís De Andrade Martins (2013)
A descriptive, analytical and cross-quantitative approach, which aimed to assess the quality of life (QOL) of women with breast cancer, which were at different times of treatment: chemotherapy or hormone therapy, and also sought to describe the characteristics sociodemographic, clinical and therapeutic study of patients and to investigate the association between this construct with socio demographic, clinical and therapeutic variables, for the entire sample under study. The sample consisted of 72 women, 25 and 47 undergoing chemotherapy in hormone therapy, which were undergoing treatment in a oncology unit located in Alfenas/MG. Data collection occurred from March 8 to November 8, 2012, with two instruments: a first for the characterization of the respondents according to sociodemographic, clinical and therapeutic variables, and the FACT B +4 to assess QOL. For both treatments discussed, it has been found, in general, good results QOL. For the total sample, found satisfactory results for all domains of the FACT B +4 and Total FACT B; being found best average scores in domain additional concerns with the arm (15,56/20) and well-being emotional (19,06/24). The domain additional concerns with breast cancer had the lowest mean score (23,26/36). In the analysis of the association between QOL and sociodemographic, clinical and therapeutic factors, the variables: sexually active, lymphedema and type of surgery, showed statistically significant associations. Women who denied sexually active had lower QOL domains in social/family well-being (p=0,001), functional well-being (p=0,005) and FACT B Total (p=0,013). The inferred presence of lymphedema in lower QOL for the domains: social/family well-being (p=0,019), emotional well-being (p=0,002), additional concerns with the arm (p=0,000) and for the FACT B Total (p=0,015). For the types of surgery, it was found positive and significant correlation for the domain functional well-being (r=0,299, p=0,011), whereas women undergoing surgery and modified radical lymphadenectomy showed a greater commitment. The health professional should be positioned in the performance of a service that aims to provide the woman with breast cancer, the continued satisfaction with their QOL in all dimensions that involve this aspect.